Pigou Pushes Preferences: Decarbonisation and Endogenous Values - Linus Mattauch; Cameron Hepburn; Nicholas Stern (Center for Economic Studies and ifo Institute (CESifo), 2018)
Avoiding unmanageable climate change implies that global greenhouse gas emissions must be reduced rapidly. A significant body of literature shows that policy instruments such as carbon prices can make an important contribution to this goal. In contrast, changes in preferences or values are rarely considered, even though other major socioeconomic transitions - such as those from reducing smoking and drink-driving - have succeeded partly because values have changed. This article examines the impact of climate policy-induced changes in consumers' values. We demonstrate that when changes in values through policies occur, and are not accounted for, such policies are inefficient. First, target-achieving carbon taxes must be adjusted if they crowd-in or -out social preferences. Second, when the urban built environment changes mobility preferences, low-carbon infrastructure investments are more valuable. Third, policy-induced changes in preferences for active travel and low-meat diets could increase the net benefits of the transition to zero emissions, in turn affecting optimal policy.
Keywords: A12; D91; H23; Q54; Q58; 330; climate change; carbon pricing; endogenous preferences; crowding-in; transport infrastructure; health co-benefit